Transcriptome analysis of Pseudomonas sp. from subarctic tundra soil: pathway description and gene discovery for humic acids degradation - Kim, Dockyu; Park, Ha Ju; Sul, Woo Jun; Park, Hyun (Folia microbiologica, 2018)
Although humic acids (HA) are involved in many biological processes in soils and thus their ecological importance has received much attention, the degradative pathways and corresponding catalytic genes underlying the HA degradation by bacteria remain unclear. To unveil those uncertainties, we analyzed transcriptomes extracted from Pseudomonas sp. PAMC 26793 cells time-dependently induced in the presence of HA in a lab flask. Out of 6288 genes, 299 (microarray) and 585 (RNA-seq) were up-regulated by > 2.0-fold in HA-induced cells, compared with controls. A significant portion (9.7% in microarray and 24.1% in RNA-seq) of these genes are predicted to function in the transport and metabolism of small molecule compounds, which could result from microbial HA degradation. To further identify lignin (a surrogate for HA)-degradative genes, 6288 protein sequences were analyzed against carbohydrate-active enzyme database and a self-curated list of putative lignin degradative genes. Out of 19 genes predicted to function in lignin degradation, several genes encoding laccase, dye-decolorizing peroxidase, vanillate O-demethylase oxygenase and reductase, and biphenyl 2,3-dioxygenase were up-regulated > 2.0-fold in RNA-seq. This induction was further confirmed by qRT-PCR, validating the likely involvement of these genes in the degradation of HA.
Keywords: Gene Expression Regulation, Bacterial; Tundra; databáze proteinů; Metabolic Networks and Pathways; biodegradace; Pseudomonas; Humic Substances; bakteriální geny; metabolické sítě a dráhy; stanovení celkové genové exprese; regulace genové exprese u bakterií; půdní mikrobiologie; Biodegradation; Degradation pathway; Databases, Protein; tundra; Humic substances; Soil Microbiology; huminové látky; Biodegradation, Environmental; lignin; Genes, Bacterial; Low temperature; Lignin; Soil bacteria; Gene Expression Profiling